Therapeutic potential of sulforaphane in liver diseases: a review - Yan, Liang; Yan, Yachun (Frontiers in Pharmacology, 2023)
The burden of liver diseases has been increased rapidly worldwide over the past decades, such as metabolic associated fatty liver diseases and hepatocellular carcinoma.However, pharmacological therapies for these liver diseases are insufficient. Sulforaphane (SFN), an isothiocyanate that is mainly found in cruciferous vegetables, has been found to have a broad spectrum of activities like antioxidation, antiinflammation, anti-diabetic and anticancer effects. Recently, a growing number of studies have reported that SFN could significantly ameliorate hepatic steatosis and prevent the development of fatty liver, improve insulin sensitivity, attenuate oxidative damage and liver injury, induce apoptosis and inhibit proliferation of hepatoma cells through multiple signaling pathways. Moreover, many clinical studies have demonstrated that SFN is harmless to human body and well-tolerated by individuals.These emerging evidences suggest SFN to be a promising drug candidate in the treatment of liver diseases. Nevertheless, limitations are existed in the development of SFN as a hepatoprotective drug due to its special properties, including instability, water insolubility, and high inter-individual variation of bioavailability when used as broccoli sprout extracts. Herein, we comprehensively reviewed recent progress of SFN in the treatment of common liver diseases and the underlying mechanisms, which aimed to provide a better understanding of the therapeutic potential of SFN in liver diseases.